Asuhan Keperawatan Gerontik Pada Pasien Diabetes Melitus Dengan Intervensi Pemberian Rebusan Daun Sirih Merah (Piper Ornatum) Untuk Menurunkan Kadar Glukosa Darah Di KP. Periuk Kota Tangerang - Nunung Sri Haryati; Siti Robeatul Adawiyah; Hasan Basri (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia due to abnormalities in insulin secretion, insulin action, or insulin secretion. The prevalence of diabetes in the population aged 20-79 years based on region in 2019 globally reached 8.3% and Southeast Asia was in 3rd place (11.3%). Indonesia is ranked 7th among the 10 countries with the highest number of sufferers, namely 10.7 million. From the data obtained by the author, diabetes mellitus is one of the 10 biggest diseases in the Periuk Jaya Health Center, the number of which increases every year. From data obtained in 2023, January-December, there were 672 diabetes mellitus sufferers. To avoid disease complications in diabetes mellitus sufferers, it is necessary to control or reduce blood sugar levels. Controlling blood sugar levels for diabetes mellitus, apart from using diabetes medicines, you can also use more natural traditional plants, namely consuming red betel leaves. Method: Case study using nursing care for Mrs. S by giving boiled red betel leaves for 7 days. Result: This red betel leaf decoction provides significant results for controlling blood sugar levels for diabetes mellitus sufferers.